DRY SLIDING WEAR BEHAVIOR OF DIFFUSION BONDED AZ-91 MAGNESIUM ALLOY REINFORCED WITH SIC PARTICLES - N, Ramanujam; M, Rajamuthamilselvan; S, Sathish (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Magnesium composites reinforced with 2, 4, 6 Wt.% of silicon carbide particles at different particle size of 10, 25 and 45 mm was synthesized using diffusion bonding process. Further the samples for scanning electron microscopic analysis and tribological analysis were made from the composites. Dry sliding wear test was carried out with L27 orthogonal design array on pin on disc tribometer. Mass loss of the pins was measured and wear rate was calculated. A statistical analysis was performed with the measured wear rate, the optimal parameter combination level was identified with main effect plot. From ANOVA analysis the significant parameters was identified.